HIITing Health in School: Can High Intensity Interval Training Be a Useful and Reliable Tool for Health on a School-Based Enviroment? A Systematic Review - Rafael Zapata-Lamana; Igor Cigarroa Cuevas; Victor Fuentes; Claudio Soto Espindola; Eva Parrado Romero; Carlos Sepulveda; Matias Monsalves-Alvarez (Shiraz University of Medical Sciences, 2019)
Context: High-intensity interval training (HIIT) is considered a time-efficient strategy to improve cardiometabolic health markers in children and adolescents. However, the evidence regarding the characterization of each intervention and the quantification of their health effects within the school environment is required. Objectives: To systematically review the characteristics of HIIT-based interventions during school time and quantify their effects on the health of children and adolescents. Data Sources: Recommendation of PRISMA for systematic review was applied. The protocol was registered in the PROSPERO repository 2018 CRD42018089017. A search of the literature (2008 - 2018) on the databases PubMed,Web of Science, CINHAL and PsycINFo was carried out. Study Selection: Twelve publications using HIIT on children and adolescents in a school-based environment were selected. The inclusion criteria were: (1) HIIT; (2) intervention and, (3) type of study. Data Extraction: The inclusion criteria to the titles and abstracts, or three independent researchers analyzed the articles. PRISMA's recommendation for systematic reviews, Cochrane tool and ROBINS for randomized and non-randomized studies were used. Results: We identified 12 studies that included a total of 917 children and adolescents; 83% of the interventions were performed during physical education classes. The average duration and intensity of the interventions were 8 weeks and > 90% HR, respectively. The most important variables evaluated and impacted by HIIT were cardiovascular fitness, nutritional status, and physiological wellbeing. Conclusions: HIIT seems to be a reliable and time-efficient approach to impact especially cardiovascular fitness of children and adolescents during school time. The focus on class intensity and the number of repetitions needs further investigation to find interventions based on each school due to individual differences regarding time and implementation constraints to impact health parameters.